Pengaruh Penggunaan Google Lens terhadap Kemandirian Belajar dan Akurasi Terjemahan Bahasa Arab - Mukhodimah, Sandia; Kholiq, Ilham Nur (Study Program of Arabic Language Teaching, 2026)
This study aims to analyze the effect of Google Lens usage on students’ self-regulated learning and Arabic translation accuracy. The research is motivated by the increasing use of artificial intelligence-based technology in Arabic language learning, which does not necessarily correspond to improvements in learning autonomy or translation quality. This study employed a quantitative, ex post facto design. The population consisted of all tenth-grade students at MAN 4 Banyuwangi in the 2025/2026 academic year, and a sample of 40 students was selected through purposive sampling. Data were collected through questionnaires measuring Google Lens usage and self-regulated learning, as well as an Arabic translation accuracy test, as the primary data sources. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, linearity testing, and simple linear regression at a 0.05 significance level. The findings indicate that Google Lens usage has no significant effect on self-regulated learning (p = 0.196; R² = 0.044) nor on Arabic translation accuracy (p = 0.290; R² = 0.029). These results suggest that AI-based translation tools require pedagogical guidance to effectively support students’ cognitive and linguistic development.